Histomorphological Spectrum of Diseases in Endobronchial Biopsy - Shrestha, Richa; Shrestha, Anil; Yogi, Subash (Journal of Nepalgunj Medical College, 2019)
Aim: To study the histomorphological pattern of disease in endobronchial biopsy in Nepalgunj Medical College Teaching Hospital (NGMCTH), Kohalpur.Background: Study of endobronchial biopsy is mainly indicated for malignancies, however, various other conditions including inflammatory pathology can be correctly identified.Material and Methods: This is a hospital based descriptive study carried out at Department of Pathology, NGMC, Kohalpur from August 2017 to July 2018. The study included 51 cases of endobronchial biopsy. All bronchial biopsies were processed according to the standard method and the detail microscopic findings were studied and the data were analysed statistically.Result: The age of patients ranged from 20-80 years. Cough was the most common presenting symptom. Most common benign pathology was tuberculosis and among malignancies squamous cell carcinoma was common histopathological diagnosis.Conclusion: Identification of lung pathology at early stage with correct histological morphology is important to decrease morbidity and mortality related to both benign and malignant condition.